STUDENT-CENTRED LEARNING (SCL) APPROACH IN EFL CLASSES - Karmila Mokoginta Mokoginta (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This article discusses Student-Centred Learning (SCL) approach. It is argued that while SCL application is related to learning activities in classrooms; it is also strongly related to the efforts of motivating learners, involving them in creating goals of learning, and encouraging them to  find the relationship between their learning and their life experience. Furthermore, it is explained that the application of SCL is partly related to cultural issues, both from teacher and learner perspectives